Flaxseed and Diabetes Management: A Comprehensive Review of Recent Studies and Potential Mechanisms - Poonam Bakhetia (International Journal of Nutritions, 2024)
Diabetes mellitus, a condition characterized by chronic hyperglycemia, has become a significant global health challenge, leading to substantial morbidity and mortality rates. Dietary techniques are crucial for the effective control of diabetes, including both pharmaceutical and non-pharmacological therapies. Flaxseed (Linum usitatissimum) is one of the functional foods that has attracted a lot of interest because of its abundance of bioactive components, including lignans, dietary fiber, and alpha-linolenic acid (ALA). The potential of flaxseed in managing diabetes stems from its capacity to enhance insulin sensitivity and glycemic control. It has high soluble fiber which slows down the digestive system’s absorption of glucose, thus helps in controlling blood sugar levels. Furthermore, the omega-3 fatty acid ALA has anti-inflammatory and cardioprotective properties that are especially helpful for diabetics who are more susceptible to cardiovascular disorders. Another essential flaxseed ingredient, lignans, has been related to better lipid profiles by lowering LDL cholesterol and enhancing general heart health, both of which are critical for people with diabetes. Numerous preclinical and clinical studies have demonstrated that flaxseed can help lower blood glucose, enhance insulin sensitivity, and reduce oxidative stress. Proposed mechanisms include enhanced beta-cell function, anti-inflammatory effects, and regulation of insulin secretion. Incorporating flaxseed to the diet in any form – whole, ground, or oil – can be a helpful tactic for managing diabetes. Still, more research is required to determine the best dosages and long-term effects. Clinical criteria must be improved before flaxseed can be considered a standard ingredient in diabetic dietary recommendations.
Keywords: Diabetes mellitus; flaxseed; glycemic control; insulin sensitivity; omega-3 fatty acid